Sustainable Crop Production - Hasanuzzaman, Mirza; Carvalho Minhoto Teixeira Filho, Marcelo; Fujita, Masayuki; Assis Rodrigues Nogueira, Thiago (IntechOpen, 2020)
This book includes twenty-one comprehensive chapters addressing various soil and crop management issues, including modern techniques in enhancing crop production in the era of climate change. There are a few case studies and experimental evidence about these production systems in specific locations. Particular focus is provided on the state-of-the-art of biotechnology, nanotechnology, and precision agriculture, as well as many other recent approaches in ensuring sustainable crop production. This book is useful for undergraduate and graduate students, teachers, and researchers, particularly in the fields of crop science, soil science, and agronomy.